0010 Bed Sharing Versus Sleeping Alone Associated with Sleep Health and Mental Health. (25th May 2022) - Fuentes, Brandon; Kennedy, Kathryn; Killgore, William; Wills, Chloe; Grandner, Michael
Abstract: Introduction: Although many adults do not sleep alone, associations between bed-sharing and sleep parameters in community samples are not well-known. The present study explored whether sharing a bed was associated with sleep duration and quality and mental health factors. Methods: Data was obtained as part of the Sleep and Health Activity, Diet, Environment, and Socialization (SHADES) study of N=1, 007 working-age adults from southeastern Pennsylvania. Bed Sharing was assessed with survey items assessing frequency in the past month of sharing a bed with a partner/spouse, child/children, pet(s), other family member(s), or nobody (sleeping alone). Other sleep health factors assessed included Insomnia Severity Index, Brief Index of Sleep Control, Epworth Sleepiness Scale, Fatigue Severity Scale, STOP-BANG apnea score, sleep duration, sleep latency, and wake after sleep onset. Mental health factors included PHQ9 depression score, GAD7 anxiety score, Multidimensional Scale of Perceived Social Support, Perceived Stress Scale, and global ratings for overall life satisfaction and relationship satisfaction. Covariates included age, sex, race/ethnicity, income, and education. Results: Compared to those who reported "Never, " those who shared a bed with a partner "Most nights" reported less insomnia severity (B=-1.60; 95%CI[-2.55, -0.66]; p=0.001), more sleep (B=0.25; 95%CI[0.02, 0.48]; p=0.035), less fatigue (B=-2.24; 95%CI[-4.10, -0.39]; p=0.018), less sleep apnea risk (B=-0.25; 95%CI[-0.42, -0.09]; p=0.003), shorter sleep latency (B=-6.32; 95%CI[-11.15, -1.50]; p=0.010) and less WASO (B=-8.69; 95%CI[-15.85, -1.52]; p=0.018). Those who slept with their child "Most nights" reported greater insomnia severity (B=2.14; 95%CI[0.65, 3.62; p=0.005), less control over sleep (B=-0.37; 95%CI[-0.59, -0.15]; p=0.001), and greater sleep apnea risk (B=0.33; 95%CI[0.07, 0.59]; p=0.012). Those who slept with other family members reported more apnea risk (B=0.44; 95%CI[0.07, 0.82]; p=0.021). Those who slept alone reported greater insomnia severity (B=2.28; 95%CI[1.28, 3.28]; p<0.0001), more sleepiness (B=0.98; 95%CI[0.22, 1.74]; p=0.011), more fatigue (B=2.87; 95%CI[0.89, 4.84]; p=0.005), and greater apnea risk (B=0.24; 95%CI[0.06, 0.41]; p=0.007). In addition, sleeping with a partner was associated with lower depression, anxiety, and stress scores, and greater social support and satisfaction with life and relationships. Sleeping with children was associated with more stress. Sleeping alone was associated with higher depression scores, and lower social support and life and relationship satisfaction. Conclusion: Sleeping with a partner/spouse is associated with better sleep quality and mental health overall. Sleeping with a child, on the other hand, was associated with worse sleep in general. Support (If Any):